Analisis Konseptual tentang Pendidikan Multikultural dalam Perspektif Islam - wildan miftahussurur; Robhitul Firdaus (LP3M KH Yazid Karimullah Institute, 2024)
Multicultural education is a vital approach to addressing cultural diversity challenges in a globalized world. From an Islamic perspective, it emphasizes not only tolerance and respect for differences but also justice and equality in educational access. This paper explores the concept of multicultural education through Islamic teachings, examining fundamental values found in the Qur'an and Hadith, as well as the thoughts of classical and contemporary Islamic educational figures. Utilizing a descriptive qualitative approach and literature review, the study analyzes the principles of multicultural education within Islam. Findings indicate that multicultural education can serve as a safeguard against radicalism and intolerance while enhancing social cohesion. However, challenges such as religious exclusivism and a lack of educational resources must be addressed. Therefore, a robust conceptual framework is necessary to integrate multicultural values into Islamic education curricula. This research aims to contribute to the development of inclusive educational models that align with the spirit of multiculturalism in Indonesia.